Antihypertensive Medication Adherence and Related Factors among Elderly Hypertensive Patients in China: A Meta-analysis - Haiyan Liu; Xueqin Zuo; Zhikai Zhou; Yina Ma; Bin Wang; Xiuquan Shi (Indian Journal of Public Health)
Background: Hypertension is one of the most common chronic diseases among elderly people, while medication adherence is associated with a decreased risk of complications in elderly hypertensive patients. Objectives: The purpose of this meta-analysis was to estimate the adherence to antihypertensive medication and related factors in elderly hypertensive patients in China. Materials and Methods: The databases served to retrieve the relevant literature before May 31, 2023. A systematic review (PROSPERO-CRD 42021278970) was conducted in accordance with PRISMA (Preferred Reporting Item for Systematic Reviews and Meta Analyses). Subgroup analysis, I2 statistics, publication bias, and quality assessment were conducted. Results: The prevalence of medication adherence among old hypertensive patients in China was 43% (95% confidence interval [CI]: 37%–49%). Medication adherence was related to education level (odds ratio [OR] = 2.12, 95% CI: 1.46-3.08), marriage (OR = 1.37,95% CI: 1.09–1.72) and the nonpresence of comorbidities (OR = 1.55, 95% CI: 1.11-2.16), but not related to the course of the disease ≤5 years (OR = 0.91,95% CI: 0.67-1.24). Adherence to antihypertensive medication among the old hypertensive population in China was moderate. Conclusion: Healthcare professionals should attach importance to older hypertension patients with low level of education and no spouse.